Transient Splenial Lesion of the Corpus Callosum Related to Migraine with Aura in a Pediatric Patient - TÜRKDOĞAN, DİLŞAD (My University, 2016)
Background: Transient splenial lesions of the corpus callosum are rare radiological findings first described in association with epilepsy, antiepileptic drugs and viral encephalitis. However, subsequently more cases were described associated with diverse clinical conditions. Case report: We describe a 13-year-old girl suffering from migraine with aura presenting with headache, right-sided hemiparesis and encephalopathy. Brain magnetic resonance imaging revealed an ovoid lesion in the splenium of the corpus callosum. The patient’s neurological symptoms resolved within 3 days without therapy and the lesion disappeared in follow up magnetic resonance images obtained 3 weeks after the onset of the symptoms. Results: Migraine with aura was considered to be the cause of the lesion. To our knowledge the present case is the first report of a pediatric patient with a diagnosis of migraine with aura presenting with hemiparesis and encephalopathy. Conclusions: A diagnosis of transient lesion of the corpus callosum should be suspected in patients with migraine with aura presenting with hemiparesis and encephalopathy. A mild course and a good prognosis might be expected in the presence of a splenial lesion of the corpus callosum.